MULTIMODAL INPUTS FOR COMPUTER-GENERATED REALITY - DESAI, Ranjit; NOORKAMI, Maneli (2023)
Implementations of the subject technology provide determining an operating mode of an electronic device based at least in part on whether the electronic device is communicatively coupled to an associated base device. Based on the determined operating mode, the subject technology identifies a set of input modalities for initiating a recording of content within a field of view of the electronic device. The subject technology monitors sensor information generated by at least one sensor included in, or communicatively coupled to, the electronic device. Further, the subject technology initiates the recording of content within the field of view of the electronic device when the monitored sensor information indicates that at least one of the identified set of input modalities has been triggered.